Evaluation of two varnishes by accelerated weathering applied to plantation timber - Rivera-Nava, Juana Laura; Borja de la Rosa, Amparo; Corona-Ambriz, Alejandro; Flores-Velázquez, Rogelio; Machuca Velasco, Roberto (Instituto de Ecología, A.C., 2016)
In this study, we determined the lifespans of two wood finishing systems, one water-based and another solvent-based, using an accelerated process of weathering. The varnishes used were both of the brand Polyform ® (Hydroform ® and 11000 ®). We applied these to wood of Cedrela odorata L. (red cedar) and Roseodendron donnell-smithii (Rose) Miranda (primavera) from commercial plantations of seven years in the state of Veracruz, Mexico. The lifespans of the varnishes were estimated with the Weibull cumulative distribution function. The varnish Hydroform® lasted 1.02 years on red cedar and 2.18 years on primavera, while the varnish 11000 ® lasted 3.70 years on red cedar and 8.99 years on primavera. According to the lifespans estimated for the two varnishes used in this study, we recommend using the varnish 11000 ® rather than Hydroform® for outdoor uses.